Anion Exchange of Ni–Co Layered Double Hydroxide (LDH) Nanoarrays for a High‐Capacitance Supercapacitor Electrode: A Comparison of Alkali Anion Exchange and Sulfuration - Zou, Wenru; Guo, Wenxin; Liu, Xinyi; Luo, Yunli; Ye, Qinglan; Xu, Xuetang; Wang, Fan (Chemistry : a European journal, 2018)
A facile and new anion exchange process is presented, which involves the conversion of NiCo‐CO3 layered double hydroxide (LDH) nanosheet arrays in an alkaline solution. The anion exchange between CO32− and OH− results in the construction of a reservoir for OH− anions, and the decoration of thin nanoflakes on the surface of nanosheets effectively enlarges the surface area of NiCo LDH nanoarrays. The capacitance of the as‐soaked NiCo LDH nanoarrays electrode increases from 1.78 F cm−2 (684 F g−1) to 6.22 F cm−2 (2391 F g−1) at 2 mA cm−2 after soaking for 12 h. Moreover, the soaked NiCo‐OH LDH electrode exhibits an enhanced rate capacity, high coulombic efficiency, and good cycling stability compared with the Ni–Co‐S nanosheet electrode synthesized through a hydrothermal sulfuration process. The as‐assembled all‐solid‐state NiCo LDH//active carbon asymmetric supercapacitor shows a maximum energy density of 83.4 W h kg−1 at a power density of 1066 W kg−1. Supercapacitor electrodes: Anion exchange is used to enhance the diffusion of OH− of layered double hydroxide (LDH) nanoarrays to achieve promising capacitive performance for supercapacitors (see figure).